Intradiskal Extravasation with Low-Volume Cement Filling in Percutaneous Vertebroplasty - Syed, Mubin I. (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Adjacent fracture formation after percutaneous vertebroplasty has been reported in literature. The purpose of this study was to determine whether intervertebral disk extravasation is related to adjacent fracture formation in low-volume cement-filling vertebroplasty. METHODS: A retrospective analysis of 308 patients having vertebroplasty was undertaken. Anteroposterior and lateral procedural fluoroscopy radiographs were analyzed for mild, moderate, or severe disk extravasation. Symptomatic refracture location relative to the presence or absence of extravasation was analyzed on follow-up fluoroscopy radiographs. RESULTS: Of the 308 patients in the study, 81 patients had disk extravasation at a total of 85 vertebral levels; 40 levels had mild extravasation, 38 levels had moderate extravasation, and 7 had severe extravasation. Of the 40 levels with mild extravasation, 6 new adjacent fractures occurred next to the disk leakage. Of the 38 with moderate extravasation, 6 new adjacent fractures occurred. Of the 7 levels of severe extravasation, only one new adjacent fracture occurred. Hence, a total of 13 adjacent fractures occurred next to disk extravasation; 13 nonadjacent fractures also occurred in the patients with disk extravasation. In the patients without disk extravasation, 28 adjacent and 24 nonadjacent subsequent fractures occurred. The average available cement volumes injected into vertebral bodies causing disk leakage ranged from 4.78 to 5.60 mL. CONCLUSIONS: With low-volume cement-filling percutaneous vertebroplasty, we cannot conclude (level of significance α = .05) that for patients who have a new fracture there is significance between the location of the fracture and the occurrence of disk extravasation.